Guillain-Barré Syndrome Triggered by Tetanus Vaccination during Pregnancy: A Rare Case Report - Jagannath Dhadwad; Prince Yadav; Kunal Modi; Bana Reddy; Chandan Kumar Dash (Journal of Clinical and Diagnostic Research)
Guillain-Barré Syndrome (GBS) following tetanus immunisation during pregnancy is an extremely rare occurrence. GBS is an autoimmune disorder in which the immune system targets peripheral nerves, causing muscle weakness and in extreme cases, paralysis. GBS after vaccination, especially after the tetanus, diphtheria and pertussis (Tdap) vaccine, is extremely rare. Here, a case of 21-year-old woman (G2A1, gravida 2, abortion 1) with acute onset of bilateral symmetrical ascending paralysis with areflexia in both upper and lower limbs, with a prior history of Tetanus vaccination 15 days back is described. The patient was examined thoroughly and all other causes were ruled out. Management of this patient was challenging, as it required treating the GBS along with ensuring the wellbeing of the foetus. The aetiological diagnosis also posed a challenge, as there was no clear history of any incriminating cause. Intravenous Immunoglobulins (IVIG) and physiotherapy were given which led to an improvement in the patient's condition. Although the routine practices followed in pregnancy, like vaccination, is vital, this case highlights the potential complications of the same. Reporting such cases is essential to enhance understanding of vaccine safety and guide future recommendations. The clinical implications enforce the need for early diagnosis and prompt management to ensure favourable outcomes for both the mother and foetus.